2015
DOI: 10.22459/her.21.02.2015.06
|View full text |Cite
|
Sign up to set email alerts
|

Are There Relationships Among Racial Segregation, Economic Isolation, and Proximity to Green Space?

Abstract: Prior research has investigated differences in exposure to green space between racial and economic groups across the United States. Results have generally shown that people of color and lower-income groups tend to live in neighborhoods with less green space than their more-advantaged counterparts. Our research extends existing studies by measuring the association between racial and economic differences in exposure to green space and racial or economic segregation across neighborhoods within cities. Findings sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The message from these findings is that it is important for city and county municipal environmental risk managers to organize community meetings in many local communities in their jurisdiction to capture all demographically diverse sectors. Other studies showed that racially segregated minority communities receive significantly fewer benefits associated with high-quality environmental planning (Glaeser & Glaser, 2010;Saporito & Casey, 2015). This study shows that racially segregated minority communities were interested in environmental issuesdemonstrated by their equal participation in flood risk management meetingscompared to racially segregated majority communities.…”
Section: Discussionmentioning
confidence: 49%
“…The message from these findings is that it is important for city and county municipal environmental risk managers to organize community meetings in many local communities in their jurisdiction to capture all demographically diverse sectors. Other studies showed that racially segregated minority communities receive significantly fewer benefits associated with high-quality environmental planning (Glaeser & Glaser, 2010;Saporito & Casey, 2015). This study shows that racially segregated minority communities were interested in environmental issuesdemonstrated by their equal participation in flood risk management meetingscompared to racially segregated majority communities.…”
Section: Discussionmentioning
confidence: 49%
“…Past research largely argues that exposure to natural environments does improve mental health and well-being, making possible limitations especially important to examine, as this study finds no significant relationship (Atuoye et al 2019;Bingley 2013;Francis et al 2012;Gesler 1992;Kaplan 2001;Saporito and Casey 2015;Volker and Kistemann 2013). The first area to consider is how this study is different than past studies.…”
Section: Limitations and Future Researchmentioning
confidence: 63%
“…Considering why white people report worse mental health is crucial to untangling these findings. Past research shows that functionality and quality of amenities lead to better well-being or mental health, and that these features are more likely to be located in largely white areas (Downey and van Willigen 2005;Fitzpatrick and LaGory 2003;Saporito and Casey 2015). Therefore, it is unlikely that residential features could explain the racial difference in mental health found in the multivariate regression.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations